Self-portrait in three colors : Gregory of Nazianzus's epistolary autobiography - Storin, Bradley K. (Christianity in late antiquity (North American Patristics Society), 2019)
"Gregory of Nazianzus (ca. 330-390 C.E.) is the earliest known Greek writer to collect and publish his own letters. Students and scholars may know him for his theological contributions, but his genius also extended into literary composition. This book builds a provocative case that Gregory's self-published letter collection constitutes not an epistolary archive, but an autobiography in epistolary form--a single text composed to secure his status among provincial contemporaries and his legacy among later generations of readers. As an autobiographical text, the letter collection utilizes self-presentational strategies that tap into late antique elite ideals in order to shore up Gregory's personal authority. The first chapter situates Gregory's publication of the letter collection within three contexts: his life, ancient autobiographical literature, and the history of Gregory's reception among his later biographers. The second examines the collection's textual history (printed editions and manuscripts) and argues for reconceptualizing its organization and thematic architecture. The third, fourth, and fifth chapters focus on the collection's three self-presentational currents--mastery of eloquence, philosophical supremacy, and friendship with Saint Basil of Caesarea. Despite not holding any office within the church at the time of publication, the letter collection and its self-presentational motifs gave him the tools he needed to construct a personalized authority"--Provided by publisher.